Development of Guided Inquiry-Oriented Worksheets to Improve Students' Metacognitive Skills on Acid-Base Material - Winarseh, Isti Indra; Azizah, Utiya (Jurnal Pendidikan MIPA, 2023)
Improving students' metacognitive skills is needed to improve the quality of education in Indonesia. The purpose of this study was to develop guided inquiry-oriented student worksheets to assist students in improving metacognitive skills on acid-base materials. The Borg and Gall model was used in this research method. The instruments used were the validation sheet, student response questionnaire, student activity observation sheet, metacognitive skills pretest-posttest questionnaire, and metacognitive inventory questionnaire. The subjects of this study amounted to 22 students of class XI IPA 1 SMAN 1 Dawarblandong. The worksheets developed were very valid with the average results of content validity on students’ worksheets 1, 2, and 3 of 4.67; 4.56; 4.56, and construct validity on students’ worksheets 1, 2, and 3 of 4.63. The practicality of the student worksheet obtained a percentage of 93.2% in the very practical category. The student worksheet was assessed for effectiveness using the N-gain test and paired sample t-test on pretest-posttest results. The average N-gain was 0.63 with a medium category and sig (2-tailed) value of 0.000 <0.05. Based on these findings, it can be said that the guided inquiry-oriented student worksheets are valid, very practical, and effective in helping students improve their metacognitive skills.Keywords: students’ worksheet, guided inquiry, metacognitive skills, acid-base.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp310-323